Experience of a partial discharge problem of electrical cables in power plant - Kongdang, P.; Nganpitak, T.; Sontayananon, N.; Chamnong, C.; Chuayin, C.; Pattanadech, N. (My University, 2018)
This paper represents a Partial Discharge ("PD") problem occurred in 6.6 kV electrical cable systems in a power plant. During annual switch gear and cable termination box inspection, some parts of electrical cables were identified as burned. Using electromagnetic and PD theory, the burned electrical cables were caused by the touching and pressing of different phase cables with inadequate clearance space. The initial solutions were rearranging the cables, using heat shrink tube for jacketing to improve the cable insulation. Inspection window was installed for PD measurement with Transient earth voltage method. Periodical PD monitoring has been performed to follow up whether new cable rearrangement can reduce the problem. The core of this problem could be better and deeper understood by Root Cause Analysis (RCA). Extension of busbar, enlargement of the cable box for better arrangement and addition of environmental control was later applied with a satisfactory outcome.
Keywords: Cable; Partial discharge; PD measurement; Transient Earth Voltage